A manual of laboratory and diagnostic tests - Fischbach, Frances Talaska (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
"Now in its Eighth Edition, this leading comprehensive manual helps health professionals deliver safe, effective, and informed care for patients undergoing diagnostic tests and procedures. The book covers a broad range of laboratory and diagnostic tests and studies that are delivered to varied patient populations in varied settings. Tests are grouped according to specimen and function/test type. Each test is described in detail, with step-by-step guidance on correct procedure, tips for accurate interpretation, and instructions for patient preparation and aftercare."--BOOK JACKET.